Plasmid-mediated quinolone resistance (PMQR) and mutations in the topoisomerase genes of Salmonella enterica strains from Brazil - Ferrari,Rafaela (2013)
The objective of this study was to identify mutations in the Quinolone Resistance Determining sources Regions (QRDR) of the gyrA, gyrB, parC, and parE genes and to determine if any of the qnr variants or the aac(6')-Ib-cr variant were present in strains of Salmonella spp. isolated in Brazil. A total of 126 Salmonella spp. strains from epidemic (n = 114) and poultry (n = 12) origin were evaluated. One hundred and twelve strains (88.8%) were resistant to nalidixic acid (NAL) and 29 (23.01%) showed a reduced susceptibility to ciprofloxacin (Cip). The mutations identified were substitutions limited to the QRDR of the gyrA gene in the codons for Serine 83, Aspartate 87 and Alanine 131. The sensitivity to NAL seems to be a good phenotypic indication of distinguishing mutated and nonmutated strains in the QRDR, however the double mutation in gyrA did not cause resistance to ciprofloxacin. The qnrA1 and qnrB19 genes were detected, respectively, in one epidemic strain of S. Enteritidis and one strain of S. Corvallis of poultry origin. Despite previous detection of qnr genes in Brazil, this is the first report of qnr gene detection in Salmonella, and also the first detection of qnrB19 gene in this country. The results alert for the continuous monitoring of quinolone resistance determinants in order to minimize the emergence and selection of Salmonella spp. strains showing reduced susceptibility or resistance to quinolones.